Battling a Common Enemy: Joining Forces in the Fight against Sewage Pollution. (22nd April 2019) - Wear, Stephanie L
Abstract: The health of both coral reefs and people are imperiled by a local threat that is widespread across the globe—sewage and the typical components it carries (e.g., nutrients, sediments, heavy metals, endocrine disruptors, pathogens, and pharmaceuticals). Despite this common threat, those concerned with human health and those concerned with coral reef health have rarely joined forces. To jump-start an alliance between coral conservation and human health sectors, this article documents the threats that humans and reefs face and identifies threat-abatement strategies that will benefit both people and reefs, highlighting the mitigation of water pollution as a prime example. By joining forces, marine conservationists and human health practitioners can increase the amount and efficiency of both intellectual and financial resources they bring to bear against sewage.